2021
DOI: 10.3390/s21155078
|View full text |Cite
|
Sign up to set email alerts
|

Can Intraoperative Intra-Articular Loads Predict Postoperative Knee Joint Laxity Following Total Knee Arthroplasty? A Cadaver Study with Smart Tibial Trays

Abstract: Ligament balancing during total knee arthroplasty (TKA) often relies on subjective surgeon experience. Although instrumented tibial trays facilitate an objective assessment of intraoperative joint balance through quantification of intra-articular joint loads, postoperative clinical assessment of joint balance relies on passive stress tests quantifying varus–valgus joint laxity. This study aimed at correlating the intraoperative and postoperative metrics used to assess joint balance while also comparing joint l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For each specimen, full leg radiographs and magnetic resonance images were acquired first. Afterwards, specimens were prepared following a standardized and validated procedure commonly applied for knee-joint simulator experiments at our institution [20][21][22][23]. Rigid marker frames with reflective spheres were attached to the tibia and femur using bicortical bone pins.…”
Section: Experimental Data Collectionmentioning
confidence: 99%
“…For each specimen, full leg radiographs and magnetic resonance images were acquired first. Afterwards, specimens were prepared following a standardized and validated procedure commonly applied for knee-joint simulator experiments at our institution [20][21][22][23]. Rigid marker frames with reflective spheres were attached to the tibia and femur using bicortical bone pins.…”
Section: Experimental Data Collectionmentioning
confidence: 99%
“…A study on VERASENSE’s accuracy confirmed this by finding that the biases for loading in the areas outside of the sensing area were more than two (outer anterior) and three (outer posterior) times greater than that of loading within the sensing area [ 21 ]. Additionally, VERASENSE was only calibrated to withstand passive forces, up to 310 N (69.7 lbf) and eLibra 300 N (67.4 lbf) in each compartment, and therefore, when research was being carried out on active loading, the devices were no longer reliable [ 22 ].…”
Section: Introductionmentioning
confidence: 99%